Extreme learning machine model for state-of-charge estimation of lithium-ion battery using gravitational search algorithm - Hossain Lipu M.S.; Hannan M.A.; Hussain A.; Saad M.H.; Ayob A.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation; Charging (batteries); Electric vehicles; Estimation; Ions; Knowledge acquisition; Learning algorithms; Lithium-ion batteries; Machine learning; Radial basis function networks; Back-propagation neural networks; Electric vehicle drive cycles; Extreme learning machine; Gravitational search algorithm (GSA); Gravitational search algorithms; Lithium ions; Radial basis function neural networks; State of charge; Battery management systems